Law and economics - Posner, Richard A; Parisi, Francesco (Edward Elgar, 1997)
These three volumes, sold in a set, offer a selection of important articles in law and economics literature, written by scholars who include Ronald Coase, Robert Cooter, Henry Manne, Steven Shavell and Oliver Williamson. The articles are arranged by theme into 12 sections.
International library of critical writings in economics ; 81
Elgar reference collection
Keywords: ekonomika; právo, zákonodárství; Economics; ekonomie, ekonomika, ekonomika zdravotnictví; právní vědy; Jurisprudence